BOVINE DYSTOCIA IN IRAQ TYPES AND TREATMENTS - J. Khammas, D.; M. AL-Hamedawi, T. (The Iraqi Journal of Veterinary Medicine, 2022)
Study was conducted on 149 case of cross breed bovine dystocia referred to Department of Theriogenology, College of Veterinary Medicine and Al-Wihda Cattle station, Baghdad, Iraq. Results showed that 87.5% of bovine dystocia were successfully relieved by cesarean section (C.S), 85.5% success was achieved by correction an traction, 71.4% by fetotomy and 50% by hormonal treatment. Most of the cases subjected to C.S, were heifers. Details concerning number of cases subjected to C.S, indications, positive response, state of pregnancy, number of claves recovered, number of male/female and survival rate of claves were listed in two enclosed tables. From results we may conclude that C.S was the best indicative treatment of dystocia, particularly when all the trails and efforts of treatments failed, inspite of the reasonable results obtained from various treatments mentioned in other cases